Multimodal teaching evaluation with a portfolio in a tertiary education language classroom - Martínez Lirola, María (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Our society has become more technological and multimodal, and consequently teaching has to be adapted to the demands of society. This article analyses the way in which the subject English Language V of the English Studies degree at the University of Alicante combines the development of the five skills (listening, speaking, reading, writing and interacting) evaluated through a portfolio with multimodality in the teaching practices and in each of the activities that are part of the portfolio. The results of a survey prepared at the end of the 2015–16 academic year show the main competences that university students develop thanks to multimodal teaching and the importance of tutorials in this kind of teaching.